Pengaruh Dewan Pengawas Syariah, Komite Audit, Kepatuhan Syariah Terhadap Persistensi Laba - Susi Susanti Bambang; Agus Munandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the influence of Sharia supervisory board, audit Committee, and sharia compliance to earnings persistence. This research uses quantitative data from sharia bank companies registered with financial services authority from 2014 – 2018. The number of populations and samples for this study was as many as 14 companies and in this study used the saturated sample techniques. The research uses regression methods and uses the Eviews 9 application. The results showed that sharia supervsory boards positively influence the earnings persistence, the audit committee positively influence the earnings persistence, and sharia compliance posittively influence the earnings persistence.